2019
DOI: 10.1126/sciadv.aau7196
|View full text |Cite
|
Sign up to set email alerts
|

Engineered botulinum neurotoxin B with improved binding to human receptors has enhanced efficacy in preclinical models

Abstract: We report the preclinical characterization of two engineered botulinum neurotoxin serotype B proteins with significant therapeutic potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 46 publications
5
46
0
Order By: Relevance
“…This is consistent with clinical observations suggesting that BoNT/B may have advantages over BoNT/A in treating disorders involving smooth muscles and the autonomic nervous system [60,63]. Thus, BoNT/B MY may offer a higher therapeutic efficacy than BoNT/A for treating smooth muscle-related disorders [62].…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations
“…This is consistent with clinical observations suggesting that BoNT/B may have advantages over BoNT/A in treating disorders involving smooth muscles and the autonomic nervous system [60,63]. Thus, BoNT/B MY may offer a higher therapeutic efficacy than BoNT/A for treating smooth muscle-related disorders [62].…”
Section: Introductionsupporting
confidence: 89%
“…Interestingly, BoNT/B and BoNT/B MY showed a higher potency than BoNT/A in paralyzing bladder muscles, which are smooth muscles [62]. This is consistent with clinical observations suggesting that BoNT/B may have advantages over BoNT/A in treating disorders involving smooth muscles and the autonomic nervous system [60,63].…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…Although there are minor sequence differences between SYT1 and SYT2 N-terminal domains, the affinity of BoNT/B for rat SYT2 is more than 2 orders of magnitude higher than for rat SYT1 (16). Interestingly, however, a single amino acid difference between rat and human SYT2 drastically diminishes BoNT/B binding affinity for the latter and consequently SYT1 is considered to be the major receptor for BoNT/B in humans at NMJ (17) and autonomic nerve terminals (18). X-ray crystallography has shown that the trefoil C-terminal domain of BoNT/B carries 2 vicinal but independent binding pockets.…”
Section: Significancementioning
confidence: 98%